Special Focus Introduction. Set Up and Shut Out: Immigration and Criminality in Contemporary Spanish Fiction - Diana Aramburu; Jeffrey K Coleman (Studies in 20th & 21st Century Literature, 2019)
The beginning of the twenty-first century has seen mass immigration from the Global South to the Global North. Unfortunately, the geopolitical and racial dynamics of this migration flow often lead to a purported nexus between immigration and criminality. In immigrant-receiving nations, this is especially the case, where sometimes the government, the media, and even the population support a xenophobic perspective based on the interconnection between immigration and criminality. Spain serves as an interesting case study for understanding how cultural productions reflect and/or critique that tendency because between 2000 and 2010 it had the world's second largest net immigration rate. The large demographic shift that immigration has produced in Spain over the past three decades ultimately created a laboratory for the creation of a multiracial and multicultural nation. This special issue provides a more nuanced understanding regarding the criminalization of immigrant communities in Spanish fiction. The authors that form this special issue demonstrate how the staging of this criminalization is reworked in genres like novels, short stories, theater, and cinema to expose and problematize the purported nexus between criminality and immigration. By bringing together crime fiction and immigration studies scholars, this issue seeks to reformulate and reconsider what has been traditionally thought of as the “immigrant problem” and its relation to crime in contemporary Spanish fiction.
Keywords: immigration; crime; criminalization; criminality; Spanish literature; Spanish film; Spanish fiction